Who shows solidarity with the irresponsible? - Friedel Bolle; Jano Costard (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
In the Solidarity game lucky winners of a lottery can transfer part of their income to unlucky losers. Will losers get smaller transfers if they can be assumed to be responsible for their zero income because they have chosen riskier lotteries? Or will risk-lovers and riskaverters favor those who made the same risk-choice, leading to larger transfers within rather than between the risk-groups? While there is support for both motives in the literature, in an experiment we find that the effect of holding people responsible for their actions is overcome by behavior guided by in-group favoritism based on different levels of risk-taking. This behavior is successfully described by a variant of the social utility function suggested by Cappelen et al. (2013). – – Im Solidaritätsspiel können die glücklichen Gewinner einer Lotterie einen Teil ihres Gewinns den unglücklichen Verlierern überlassen. Erhalten die Verlierer eine geringere Kompensation, wenn sie dafür verantwortlich gemacht werden können, dass sie leer ausgingen, weil sie sich für eine riskantere Lotterie entschieden hatten? Oder bevorzugen risikofreudige und risikoscheue Spieler diejenigen, die sich für das jeweils gleiche Risikoniveau entschieden hatten? Während es in der Literatur Argumente für beide Motive gibt, zeigt sich im Experiment, dass Verlierer mehr Solidarität erfahren, wenn sie die gleiche Risikoentscheidung getroffen haben wie der Gewinner und dass damit das Motiv Spieler für ihre Entscheidung verantwortlich zu machen in den Hintergrund treten kann. Dieses Verhalten kann erfolgreich durch eine Variante der social utility function, wie sie von Cappelen et al. (2013) vorgeschlagen wurde, erklärt werden.
Keywords: D3; D8; 330; Risky Behaviour; Solidarity; Responsibility; In-Group Favoritism